SISTEM INFORMASI JASA GROOMING DAN DATA PENJUALAN BARANG PADA MEONG PET SHOP: Custody;Goods;Gromming;Returns;Sales;Stock Information Systems;Visual Basic.Net. - Afrizal , Afrizal; Andi S, Daniel Julpri (LP2M Universitas Nurdin Hamzah, 2020)
This thesis discusses the system formation in Meong Pet Shop covering gromming services and selling goods. Based on previous research by conducting survey and interview methods, the counting and recording methods at Meong Pet Shop are currently still done manually. The Meow Pet Shop Information System contains information on goods data, information on gromming service data, customer data information, deposit data information, sales data information and return data information and reports. Computerized storage will make the process easy and fast processed to facilitate employees in processing data into information in the form of reports. The application used in making this information system uses the Visual Basic.Net application. The Meow Pet Shop application is expected to reduce data duplication. This application also has reports making facilities including goods data reports, gromming data reports, deposit data reports, sales data reports, returns data reports and stock addition data reports.